2016
DOI: 10.1108/ijcma-08-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

The link between guanxi and customer–salesperson collusion

Abstract: Purpose In the insurance industry, it is common for the insurance salespeople to sell insurance products to friends, relatives and associates. However, permitting (or encouraging) salespeople to sell insurance through personal relationships may result in some ethical conflicts. For example, some insurance salespeople may help relatives or friends with pre-existing medical conditions buy the health insurance. Previous studies on insurance fraud have rarely focused on this problem. Thus, this study aims to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…In the high-quality category of collaborative environment, the provider-insurer relationship (Lin et al, 2008 ), the consumer-provider relationship (Lin et al, 2008 ), and bosses influence (Tseng & Kang, 2015 ); increased HIF. Also, in the middle-quality category, the consumer-insurer relationship (Manocchia et al, 2012 ), the Guānx i (Tseng, 2016 ), showed influence in increasing the HIF.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the high-quality category of collaborative environment, the provider-insurer relationship (Lin et al, 2008 ), the consumer-provider relationship (Lin et al, 2008 ), and bosses influence (Tseng & Kang, 2015 ); increased HIF. Also, in the middle-quality category, the consumer-insurer relationship (Manocchia et al, 2012 ), the Guānx i (Tseng, 2016 ), showed influence in increasing the HIF.…”
Section: Resultsmentioning
confidence: 97%
“… (Manocchia et al, 2012 ) Ethics and morals The health insurance market is not immune to intrapersonal processes such as ethics and the offer of moral risks, which could influence the actors’ positions and their behaviour. (Tseng, 2016 ) (Bourgeon & Picard, 2014 ; Dionne et al, 2009 ; Jou & Hebenton, 2007 ; Kumar et al, 2011 ; Tseng & Kang, 2015 ; Wang, 2014 ; Zhou et al, 2016 ) (Ribeiro et al, 2020 ) (Duszak & Duszak, 2011 ) (Lesch & Baker, 2013 ) Perception of inequity and injustice The relational dynamic produces a perception of injustice or inequity. (Ribeiro et al, 2020 ) (Lesch & Baker, 2013 ) Information asymmetry Asymmetric information occurs when one of the actors does not have the same information, this is reflected in the behaviours adopted by the different actors and their billing processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Malaysia alone, approximately RM1.384 billion claims incurred for the first quarter of 2014 due to authentic and forgery motor insurance claims (KPMG, 2010;PIAM, 2014). Findings from the past studies had shown that trust (Pauline, Esterick-Plasmeijer & Raaij, 2017) and confidence (Mazar, Amir & Ariely, 2008) which are compositions of attitude (Al-Swidi et al, 2014) are significant in determining the intention of a person to commit fraud (Tseng, 2016). Thus, this research aims to study the variables that contribute to an individual's attitude to commit motor insurance fraud.…”
Section: Introductionmentioning
confidence: 99%